Geographic information in the analysis of changes in land use and vegetation cover in the Rio Vermelho microregion (GO) - Soares, Cleonice Batista Regis; Alécio Perini (Revista Cerrados, 2023)
The geographical space presents transformations coming from the society/nature relationship, becoming the focus of discussions in the scientific community in the face of the intense process of the natural resources degradation. In this context, the evaluation of the dynamics of changes in the landscape is fundamentally important to assist territorial planning and management. Thus, the objective was to analyze changes in land use and vegetation cover in the Rio Vermelho microregion – GO, in the periods from 2000-2010 and 2010-2018. For this purpose, it was used orbital remote sensing, global positioning system, geographic information systems and the cross-tabulation methodology proposed by Pontius Jr. et. al. (2004). As results, it is highlighted the deforestation of areas of the Cerrado remnants of vegetation for the formation of pastures totaling 675.71 km² and the process of conversion of pasture areas into areas of rainfed agriculture (16.93 km²), and irrigated agriculture by central pivot (44.76 km²), directed to the commodities segment in the period between 2000-2010. For the period between 2010-2018, it is observed the continuity of the deforestation process of the remaining vegetation cover with 276.31 km² and intensification of the losses in pasture areas in 321.32 km², transformed into rainfed and central pivot agricultural areas, besides the introduction of forestry (6.76 km²) in the region as an additional commercial alternative.